1995
DOI: 10.1111/j.1476-5381.1995.tb14949.x
|View full text |Cite
|
Sign up to set email alerts
|

The protective action of chlormethiazole against ischaemia‐induced neurodegeneration in gerbils when infused at doses having little sedative or anticonvulsant activity

Abstract: Sweden1 The effect of chlormethiazole administration on delayed neuronal death in gerbil hippocampus following transient global ischaemia has been examined. Chlormethiazole was administered either intraperitoneally or by intravenous infusion with either the dose or the time of infusion varied.2 Chlormethiazole (600 pmol kg-', i.p.) given 60 min after ischaemia produced substantial (>60%) neuroprotection when damage was assessed 5, 14 or 21 days later, indicating the drug does not merely delay cell death. 3 Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
24
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 14 publications
5
24
0
1
Order By: Relevance
“…Recent animal studies have demonstrated neuroprotective properties of clomethiazole following transient global ischemia in the gerbil [1, 2] as well as temporary [3] and permanent [4, 5] focal ischemia, ischemic brain edema [6] and certain drug-induced neurotoxicities in the rat [7]. Clomethiazole is a drug with sedative properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recent animal studies have demonstrated neuroprotective properties of clomethiazole following transient global ischemia in the gerbil [1, 2] as well as temporary [3] and permanent [4, 5] focal ischemia, ischemic brain edema [6] and certain drug-induced neurotoxicities in the rat [7]. Clomethiazole is a drug with sedative properties.…”
Section: Introductionmentioning
confidence: 99%
“…We found that the metabotropic glutamate receptor agonist ACPD stimulated phosphoinositol hydrolysis in an L-AP3-dependent manner, although L-AP3 did not completely inhibit hydrolysis and, when added alone, L-AP3 had a weak stimulatory action, supporting the suggestion that it might be a partial agonist (Irving et al 1990). While clomethiazole was found to also inhibit the stimulatory effect of ACPD it did so only at a concentration (10-3M) which is unlikely to have functional relevance, given the fact that neuroprotection can be achieved in vivo at a plasma concentration of approximately lO-'M (Cross et al 1995). However not all metabotropic glutamate receptor subtypes stimulate phosphoinositol hydrolysis (Schoepp & Conn 1993), so we cannot, at present, totally exclude an interaction of clomethiazole with other metabotropic glutamate receptor subtypes.…”
Section: Discussionmentioning
confidence: 76%
“…Clomethiazole has been shown to have neuroprotective effects in rat, gerbil, and marmoset models of cerebral ischaemia [6][7][8][9][10][11][12]. These findings suggested that clomethiazole might prevent neuronal degeneration following ischaemic stroke and the drug has undergone clinical development as a potential treatment.…”
Section: Introductionmentioning
confidence: 99%